PROMOSI MELALUI MEDIA SOSIAL PADA DESTINASI WISATA AIR TERJUN BATU DINDING DI DESA TANJUNG BELIT KECAMATAN KAMPAR KIRI HULU - Fitriani, Eka; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This research examines the promotion through social media of the Batu Dinding Waterfall tourist destination in the Tanjung Belit Village, Kampar Kiri Hulu District. Given the increasing interest of tourists reflected by visitation data showing more than 10,000 tourists in 2024 in the period January to June, this research aims to explore the effectiveness of marketing strategies carried out through social media platforms such as Instagram and TikTok. Using a descriptive qualitative method approach, data was obtained through observation, interviews, and documentation, involving key informants from the Batu Dinding Tourism Awareness Group (Pokdarwis) and tourists. The results show that the promotion conducted on social media is very effective in introducing the beauty and tourism potential of Batu Dinding Waterfall to the public, especially in attracting the millennial segment who are more active in using the platform. However, this study also identified several obstacles, such as the manager's lack of understanding of digital marketing strategies and minimal budget, which hindered the implementation of optimal promotion. At the end of the research, it is recommended that Pokdarwis Batu Dinding members attend training and workshops to improve their knowledge and skills in utilizing social media, as well as the need for support from the local government to improve infrastructure and facilities that support tourism. Thus, this research is expected to contribute to the development of more effective and sustainable promotional strategies to boost tourist visits and improve the local economy. Keywords: Social media promotion, Batu Dinding Waterfall, tourism, tourism development, marketing strategy, tourists.